Exploring the Bismarck - Ballard, Robert D. (New York : Scholastic/Madison, 1991)
Recreates the sea battle that sank the German battleship Bismarck in World War II and recounts how the shipwreck was discovered in 1989.
6.9
5-8
Keywords: Underwater archaeology -- North Atlantic; Bismarck (Battleship); Shipwrecks; World War, 1939-1945 -- Antiquities; Bismarck (Battleship); Shipwrecks; World War, 1939-1945 -- Antiquities; Underwater exploration